A Whale Optimization Algorithm-Based Data Fitting Method to Determine the Parameters of Films Measured by Spectroscopic Ellipsometry - Liyuan Ma; Xipeng Xu; Changcai Cui; Mai Gao; Tukun Li; Shan Lou; Paul J. Scott; Xiangqian Jiang; Wenhan Zeng (Photonics)
A data-fitting method based on the whale optimization algorithm (WOA) is proposed to determine the thickness and refractive index of films measured by spectroscopic ellipsometry (SE). To demonstrate this method, tin oxide (SnO2) films with transparent wavelength coverage (400–800 nm) are evaluated. The comparative analysis indicates that Psi and Delta parameter curves based on WOA fitting align more closely with those obtained through experiments. Furthermore, the thickness and refractive index of films obtained by WOA are in nearly agreement with the results from the well-known Levenberg–Marquardt (LM) algorithm. This validation confirms that it has great potential in the determination of film parameters in ellipsometry data fitting.